ANALISIS STATUS SOSIAL EKONOMI, CITRA PERGURUAN TINGGI DAN KESEMPATAN KERJA TERHADAP KEPUTUSAN STUDI LANJUT KE PERGURUAN TINGGI PADA SISWA-SISWI KELAS XII MAN JOMBANG TAHUN PELAJARAN 2015-2016 - Agung, Heny; Rusli, Rusli (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
The purpose of this research is: (1) to know the influence of the following factors, namely socio-economic status, the image of College and employment opportunities of further studies into college. (2) to know the most dominant influence toward the decision for knowing some factors further studies into college. For achieving that goal, the researcher used quantitative methods to analysis of the factors. The object of this research is the students of class XII MAN Jombang Lessons year 2015-2016. The data collection techniques usedÂ are observation, question form/questionnaire, interview and documents. The data were analyzed by means of test validity, reliability test, test and test the assumptions of classical hypothesis. The results of the reserch showed that: (1) the socio-economic Status of the Factor (X1) influence of 69,3%, Image Factors of higher education (X2) influence of 0.9% and employment opportunities (X3) exert influence by 4% against the decision of further studies into College on students of class XII MAN Jombang Lessons Year 2015-2016. (2) The most dominant factor of its influence on the decision of further studies class XII students MAN Jombang Lesson Years 2015-2016 is a factor of social economic status (X1) and its influence of 69,3%.Keyword: Socioeconomic, The College, Employment